Pengaruh Kesepian Terhadap Kecanduan Game Online Pada Mahasiswa - Angga Maulana Saputra; Lukman Lukman (Jurnal Psikologi TALENTA, 2023)
The problem of online game addiction occurs in Makassar State University students, indicated by the duration of playing beyond the time limit. This study aims to determine the effect of loneliness on online game addiction in UNM students. This study uses quantitative methods. This study involved students at Makassar State University (N=385). The sampling technique in this study used cluster random sampling. The measuring instrument used is 14 item loneliness scale (specifically using emotional loneliness and social loneliness) scale from Azzahra (2018) and online game addiction scale from research (Lukman, 2020). Data analysis used in this research is the binary logistic regression technique with bootstrap method with SPSS 22.00 application. Data analysis was carried out in two directions, adjusted for loneliness which has two forms, emotional loneliness and social loneliness. On emotional and social loneliness each obtained a significance value (p) of 0.000 & 0.000 (p <0.05), so that Ho in this study was rejected. coefficient (r) for emotional loneliness is 0.560 and social loneliness is 0.582. The results of this study indicate that there is a significant positive relationship between loneliness and online game addiction in UNM students.